The Guidance and Sports Development Achievements in Sragen Regency Based Local Excellence - Sulistiyo Sulistiyo; Agus Kristiyanto; Sapta Kunta Purnama (Nicolaus Copernicus University in Toruń, 2020)
This research attempts to find out the government Sragen Regency on implementing Law No. 3 in 2005 chapter 34 about the district/city government is obliged to manage at least one superior sports national and/or international standard. This research using the methodology descriptive qualitative. Research data sources such as 2 employees DISPORA, 2 employees KONI Sragen Regency, 2 athletes and 2 coach. Data collection techniques using interviews. Data analysis techniques use descriptive analysis.          Based on the results of research can be concluded as follows: (1) the district government Sragen not implement Law No. 3 in 2005 Chapter 34, (2) KONI not focus on 1 superior sports, KONI focusing on the main tasks KONI to improve performance, (3) Executive power in increasing the achievement is coach, (4) Funding from KONI 85% directed to the development of sport and DISPORA direct funding for sports competition, (5) Infrastructures in condition enabling, (6) Coaching done through P3B program (Nursery Sustainable Development Program) and Prosukma (Gold Sukowati Program).